Alginate-based encapsulation of porcine placenta extract: Preparation, enteric sustained release, biological activities, and stability - Anukul Taweechaipaisankul; Nutthanit Thumrongsiri; Walailuk Chonniyom; Paweena Dana; Prattana Tanyapanyachon; Monthira Rattanatayarom; Wannapa Chinchoosak; Nattika Saengkrit (Food Hydrocolloids for Health)
The porcine placenta is a source of various advantageous bioactive molecules, however, the unsatisfactory appearance, together with its unsavory taste and odor, is still limiting its use as an ingredient in food products. Microencapsulation represents a promising technique to increase the use of valuable biowaste, as well as to promote its bioavailability and stability. Here, alginate microbeads containing porcine placenta extracts (pPEs) were developed by the ionotropic gelation method under various conditions, and many of their properties were tested. We found that placenta tissues prepared by freeze-drying could provide a great yield of protein derivatives and possessed 50.37 % anti-oxidative activity. Formulation 2 (F2) of alginate microbeads (80 % solution containing 2 % sodium alginate with 1 % bentonite, 20 % pPE formed in 0.5 % chitosan added into 1 % CaCl2 solution) was chosen as the optimal encapsulated condition of pPEs. Generally, the F2 microbeads contained 57.5 µg/mL of pPE with 99.72 % entrapment efficiency. The average size measured by Mastersizer was 14.65 ± 0.08 µm. The release of pPEs under simulated gastrointestinal tract conditions at pH 2.0–6.8 was delayed at 2 h (38.7 %) compared with free pPE. The F2 microbeads showed positive biological effects of anti-oxidation. Moreover, the anti-inflammation effect was monitored via the reduction in the levels of cytokines, including IL-6, IL-8, and TNF-α. The F2 microbeads maintained their protein quantities for >120 days at 25 °C. Taken together, microbead fabrication, especially F2, is the optimal formula for pPEs, showing the potential to be applied as a prospective carrier of pPEs for oral administration.